MEMPERTIMBANGKAN URGENSI PERADILAN PIDANA ANAK DALAM TINDAK PIDANA : UPAYA PERLINDUNGAN GENERASI MASA DEPAN - Rumbruren, Abdul Munir; Muhammad, Ali (Journal of Management Small and Medium Enterprises (SMEs), 2024)
Various problems carried out by children are part of the actions that result in children being entangled in legal problems, with different legal problems considered minor problems, but according to the laws and regulations constitute a criminal act. This raises various questions about whether the juvenile criminal justice system can deal with this problem effectively, how youth involved in crime should be treated, and how aspects of rehabilitation and reintegration within this system play an important role in building a better future for children. These research methods according to their types can be divided into two, namely normative legal research and empirical legal research. Empirical legal research was carried out using interviews in the field, namely by carrying out it at the Manokwari Class I correctional center to know and obtain information from parties related to the research theme being carried out. We also studied cases of children in conflict with the law, which were successfully resolved outside of legal channels through a restorative justice diversion approach. The research location selection was carried out in the West Papua area based on the reason that Manokwari is one of the cities with high levels of child crime in conflict with the law is significant and relatively increasing. The results of the research show that there are still many children who do not understand the laws that result in criminal acts, which are regulated in the law on the juvenile criminal justice system, implementing legal awareness outreach activities for school children and providing guidance and increasing understanding of the law for children in the Manokwari City area. Keywords: Criminal Justice System; Child Crime; Restorative Justice